2016
DOI: 10.1097/sih.0000000000000191
|View full text |Cite|
|
Sign up to set email alerts
|

Mode of Information Delivery Does Not Effect Anesthesia Trainee Performance During Simulated Perioperative Pediatric Critical Events

Abstract: The format (paper or electronic) of the CA did not affect the impact of the CA on clinician performance in this study. Clinician compliance with the use of the CA was unaffected by format, suggesting that other factors may determine whether clinicians choose to use a CA or not. Time to use of the CA did not affect clinical performance, suggesting that it may not be when CAs are used but how they are used that determines their impact. The current study highlights the importance of not just familiarizing clinici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 26 publications
4
11
0
Order By: Relevance
“…Subjective findings of this study found in Tables 2 and 5 demonstrate a need for familiarization, self-review, but also training on how to use the manual which correlates with previous studies [8-9]. An article regarding previous large-scale implementation in China focused on different forms of simulation training performed in China and included interactive lectures regarding why, how, and when to use emergency manuals which were included in an overall implementation movement with multiple forms of simulation including lecture, workshop, demonstrations and simulation competition [10].…”
Section: Discussionsupporting
confidence: 85%
“…Subjective findings of this study found in Tables 2 and 5 demonstrate a need for familiarization, self-review, but also training on how to use the manual which correlates with previous studies [8-9]. An article regarding previous large-scale implementation in China focused on different forms of simulation training performed in China and included interactive lectures regarding why, how, and when to use emergency manuals which were included in an overall implementation movement with multiple forms of simulation including lecture, workshop, demonstrations and simulation competition [10].…”
Section: Discussionsupporting
confidence: 85%
“…The reasons for this are unclear and with limited numbers may be solely related to individual deficiencies. However, previous studies have found that using an eDSS reduces situational awareness, diverts the user's attention away from the patient, delays life-saving interventions [26] and increases the risk of misunderstandings [24]. In keeping with these findings, our participants suggested that they were distracted; such distraction may have been caused by a lack of familiarity with the software.…”
Section: Discussionsupporting
confidence: 73%
“…The e-checklist reduced provider errors and cognitive workload without increasing checklist completion time, showing the feasibility of checklists in emergency medical settings. In contrast, Watkins et al [26] found no difference between the two formats. These studies are critical because they establish the importance of a proper design and appropriate use of cognitive aids, in addition to the format.…”
Section: Background and Related Workmentioning
confidence: 91%